2019
DOI: 10.25130/tjes.26.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Removal From Synthetic Wastewater Using Batch Adsorption Scheme

Abstract: Phenol is one of the most dangerous pollutant of petroleum industry. Thus its removal is very essential. One of the most popular method used to remove phenol is through adsorption by activated carbon. In the present work, batch adsorption experiments are carried out under various operating parameters: pollutant concentration (CO) (10, 30, and 50mg/L), and activated carbon dose (CD) (250-1500mg/1.25L with an increment of 250). All experiments are performed at laboratory temperature (19ºC) and pH of 7 ± 0.1 whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Activated carbon (AC) can be defined as a carbonaceous material which having a porous texture and well-developed surface area. As a result, AC has been commonly utilized in separation processes or catalysis and as adsorbent [13][14][15][16]. MA et al [17] studied the elimination of phenolic compounds by utilizing powder activated carbon as adsorbent in batch reactor and it was found that more than 80% of phenolic compounds was removed at 10 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated carbon (AC) can be defined as a carbonaceous material which having a porous texture and well-developed surface area. As a result, AC has been commonly utilized in separation processes or catalysis and as adsorbent [13][14][15][16]. MA et al [17] studied the elimination of phenolic compounds by utilizing powder activated carbon as adsorbent in batch reactor and it was found that more than 80% of phenolic compounds was removed at 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…MA et al [17] studied the elimination of phenolic compounds by utilizing powder activated carbon as adsorbent in batch reactor and it was found that more than 80% of phenolic compounds was removed at 10 min. In some studies, using AC modified (prepared from agricultural wastes such as palm fronds, date stones and rice husk treatment via chemical and physical activation procedure and maximum capacity of removal (84.83%-94.65%) [13]. The study of the adsorption of phenol from an aqueous solution using tamarind seed powder (TSP) with adsorption process AD was investigated [25].…”
Section: Introductionmentioning
confidence: 99%